1954
DOI: 10.1029/tr035i004p00558
|View full text |Cite
|
Sign up to set email alerts
|

Aeromagnetic surveys in the Aleutian, Marshall, and Bermuda Islands

Abstract: Total‐intensity aeromagnetic surveys of the Aleutian Marshall, and Bermuda Islands were completed in 1948. The anomalies associated with the Aleutian volcanoes are attributed mainly to topographic relief and are not an indication of the degree of volcanic activity. Eniwetok presents a magnetic pattern that would be produced by an irregular‐shaped rimmed depression in the basement, modified by the two adjoining seamounts, and differs from Bikini, whose magnetic features would be produced by a broad seamount wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 10 publications
4
18
0
Order By: Relevance
“…This anomaly has been known for some time (Keller et al, 1954) and was extensively discussed by . Because of its proximity to the continental slope, this anomaly has been referred to as the "slope anomaly" or the "continental shelf anomaly."…”
Section: Descriptionmentioning
confidence: 95%
See 1 more Smart Citation
“…This anomaly has been known for some time (Keller et al, 1954) and was extensively discussed by . Because of its proximity to the continental slope, this anomaly has been referred to as the "slope anomaly" or the "continental shelf anomaly."…”
Section: Descriptionmentioning
confidence: 95%
“…Summary of Interpretation _~______~_______ Keller et al (1954) postulated source of the anomaly as being a 4%km wide intrusive parallel to the edge of the continent. Drake et al (1959) suggested that the anomaly resulted from a basement ridge separating two sedimentary troughs.…”
Section: Referencementioning
confidence: 98%
“…The East Coast Magnetic Anomaly (ECMA) is a strong and continuous magnetic anomaly, extending from Georgia to Nova Scotia (Drake et al, 1959;Keller et al, 1954). This positive magnetic anomaly (ECMA), with amplitudes ranging from 200 to 300 nT, varies in character along the margin.…”
Section: Geodynamic and Geological Settingmentioning
confidence: 98%
“…It can be traced laterally for 600 km before terminating against or merging with the East Coast Magnetic Anomaly (ECMA), which is a 48-km-wide, through going magnetic high along the rifted Atlantic margin of Laurentia (e.g., Vogt, 1986;Klitgord and Schouten, 1986, and references therein). The ECMA, which can be traced for more than 3000 km, has been interpreted variously: as an edge effect; as a dike suite; as a series of seaward-dipping reflectors containing tilted basalt flows; and as a deep-seated mafic intrusion (e.g., Alsop and Talwani, 1984;Keen, 1969;Keller et al, 1954;Oh et al, 1995) along or near the continent-ocean transition (Vogt, 1973;Vogt and Einwich, 1979)) Nelson et al (1985a,b) and McBride and Nelson (1988) suggested the ECMA may represent a Paleozoic suture. Thus the ECMA was probably emplaced 175-190 Ma (Vogt and Einwich, 1979;Klitgord and Grow, 1980;Sheridan, 1983;Alsop and Talwani, 1984) possibly along or near the relict suture during early rifting leading to successful opening of the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%